2012
DOI: 10.1177/030006051204000629
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Changes in Components Associated with Metabolic Syndrome and Disappearance, or Remission, of Metabolic Syndrome during 1 Year

Abstract: Short-term weight reduction has no impact on the status of metabolic syndrome. The disappearance of metabolic syndrome was common during a 1-year follow-up. This finding might impact on the treatment and management of people with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…This study is the first study assessing the impact of thyroid function on the regression of dyslipidemia and its components. To our best knowledge, the disappearance of metabolic syndrome was common (30%), mainly due to a reduction in TG and an increase in HDL-C. [ 16 ] In our study, high normal FT4 levels showed an independent association with the regression of dyslipidemia, especially high TG and low HDL-C status, in adult males.…”
Section: Discussionsupporting
confidence: 52%
“…This study is the first study assessing the impact of thyroid function on the regression of dyslipidemia and its components. To our best knowledge, the disappearance of metabolic syndrome was common (30%), mainly due to a reduction in TG and an increase in HDL-C. [ 16 ] In our study, high normal FT4 levels showed an independent association with the regression of dyslipidemia, especially high TG and low HDL-C status, in adult males.…”
Section: Discussionsupporting
confidence: 52%
“…This may be attributed to the risk factors pertaining to the participants who went on a diet compared with other subjects without any special diet. Also, another reason may be changes in the risk factors that affect the components of MetS in the participants during the 10 years of the study ( 38 ) .…”
Section: Discussionmentioning
confidence: 99%